The City-State Of Madina: Administrative And Constitutional Policies Of Prophet Mohammad [PBUH] - Nasir Hassan Wani (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2023)
The Qur'an says man is the noblest of all creation. The entire universe is made for him and serves his goals. In any system, it is important to Examine the status of man in society and the role of the state in connection to the higher moral and ethical principles of life as well as the idea of the Divine Being in the social order. An administrative system that benefits its citizens' well-being is known as a welfare state. The city-state of Medina established by the Holy Prophet Mohammad [PBUH] is one of the best examples of it.  It should be remembered that the Holy Prophet (PBUH) is the final messenger sent by Allah and his ultimate mission and objective was to improve the moral and spiritual standards of the people. Therefore, God's wisdom demanded that the features of both prophethood and leadership should be combined in his personality. The life of the Prophet Muhammad (PBUH), who is the last and final messenger, can be separated into two parts: life in Makkah and life in Medina. While the former was mainly focused on the monotheistic preaching of Islam and the latter was largely concerned with the founding of the city-state of Medina.  The prophet performed various characters during the ten years of the Medina period. Muhammad (PBUH) dedicated his life to organizing and developing his newly founded state in all aspects. Its only possible structure and foundation were on Divine Guidance (Wahi), as it had to eliminate all types of ills and develop all types of values and excellencies. In this paper, we'll try to examine the prophet`s administrative and constitutional policies during the governance of the city-state of Medina.